RNA from LPS-stirnulated macrophages induces the release of tumour necrosis factor-α and interleukin-1 by resident macrophages - R. A. Ribeiro; F. L. De Lucca; C. A. Flores; F. Q. Cunha; S. H. Ferreira (Hindawi Limited, 1993)
The effect of exogenous RNA on many cellular functions has been studied in a variety of eukaryotic cells but there are few reports on macrophages. In the present study, it is demonstrated that cytoplasmatic RNA extracted from rat macrophages stimulated with Escherichia coli lipopolysaccharide (LPS), referred to as L-RNA, induced the release of TNF-α and IL-1 from monolayers of peritoneal resident macrophages. The activity of L-RNA was not altered by polymyxin B but was abolished by ribonuclease (RNase) pretreatment, indicating the absence of LPS contamination and that the integrity of the polynucleotide chain is essential for this activity. Both the poly A(−) and poly A(+) fractions obtained from L-RNA applied to oligo(dT)-cellulose chromatography induced TNF-α and IL-1 release. The L-RNA-induced cytokine release was inhibited by dexamethasone and seemed to be dependent on protein synthesis since this effect was abolished by cycloheximide or actinomycin-D. The LPS-stimulated macrophages, when pre-incubated with [5-3H]-uridine, secreted a trichloroacetic acid (TCA) precipitable material which was sensitive to RNase and KOH hydrolysis, suggesting that the material is RNA. This substance was also released from macrophage monolayers stimulated with IL-1β but not with TNF-α, IL-6 or IL-8. The substance secreted (3H-RNA) sediments in the 4-5S region of a 5-20% sucrose gradient. These results show that L-RNA induces cytokine secretion by macrophage monolayers and support the idea that, during inflammation, stimulated macrophages could release RNA which may further induce the release of cytokines by the resident cell population.